2016
DOI: 10.1590/s1678-9946201658077
|View full text |Cite
|
Sign up to set email alerts
|

A Decade Trend of Multidrug Resistant Tuberculosis in São Paulo State, Brazil

Abstract: SUMMARYThe aim of this retrospective study was to review all the notified cases of multidrug-resistant tuberculosis (MDR-TB) in São Paulo State (Brazil), as well as to describe and discuss the clinical, microbiological and radiologic aspects in a single reference center, within the same state, from 2000 to 2012. There were 1,097 notifications of MDR-TB in São Paulo State over this period, 70% affecting men aged on average 38 years (10-77). There was a significant fall in the MDR-TB mortality rate from 30% to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
4
0
2
Order By: Relevance
“…The results showed that in the state of São Paulo there was a growth in the proportion of patients’ cure and a trend to reduce treatment failure, highlighting a visible conversion of these outcomes mainly from 2011, something also observed by Valdes et al 10 . These trends are presumed to be related to the application of norms for diagnosis and treatment published in 2007, which allowed over time to reverse the state scenario of MDR-TB treatment observed between the 2006 and 2010 and to incorporate new drugs and regimens treatment in the state 11 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The results showed that in the state of São Paulo there was a growth in the proportion of patients’ cure and a trend to reduce treatment failure, highlighting a visible conversion of these outcomes mainly from 2011, something also observed by Valdes et al 10 . These trends are presumed to be related to the application of norms for diagnosis and treatment published in 2007, which allowed over time to reverse the state scenario of MDR-TB treatment observed between the 2006 and 2010 and to incorporate new drugs and regimens treatment in the state 11 .…”
Section: Discussionsupporting
confidence: 66%
“…Os resultados mostraram que no estado de São Paulo houve um crescimento na proporção de cura dos pacientes e uma tendência de redução da falência no tratamento, destacando uma visível conversão desses desfechos principalmente a partir de 2011, algo também observado por Valdes et al 10 . Presume-se que tais tendências estejam relacionadas à aplicação de normas para o diagnóstico e tratamento publicadas em 2007, que possibilitaram com o tempo reverter o cenário estadual de tratamento da TB-MDR observado entre os anos de 2006 e 2010 e incorporar novas drogas e esquemas de tratamento mais efetivos no estado 11 .…”
Section: Discussionunclassified
“…84,000 new cases were estimated in 2015 with an incidence of 41 per 100,000 and a mortality rate of 2.7 per 100,000 ( WHO 2016 ). Despite Brazil not being among the high-burden MDR-TB countries ( WHO 2016 ), the number of MDR-TB cases in Brazil identified after 2007 almost doubled (from approximately 300 cases in 2007 to 702 cases in 2014) ( Bollela et al 2016 ). In the state of Minas Gerais, the second most populated state in the southeast region of the country, the mean MDR TB rate was 0.2% among the notified TB cases between 2002 and 2009 ( Augusto et al 2013 ).…”
mentioning
confidence: 99%
“…This finding consistent with the study conducted in China, 8 , 9 however, contrary to the study conducted in India and Brazil. 12 , 13 Our findings indicated that the majority of the cases were among people aged greater than 15 years. This finding consistent with the study conducted in China and India.…”
Section: Discussionmentioning
confidence: 56%